PREVALENCE OF ANEMIA AMONG UNIVERSITY OF PESHAWAR STUDENTS - Khan, Muhammad Tahir; Akhtar, Tasleem; Niazi, Mussarat (Journal of Postgraduate Medical Institute, 2011)
Objective: Methodology: Results: Conclusion: The prevalence of anemia among girls is high as compared to boy's student. This warrants further study on a larger sample of healthy college students to validate these findings and to safeguard the health of these future mothers. The mean age of the students was 21.9+2.3 years. Out of 521 participating students anemia was prevalent in 4/262 boys (1.5%) and 62/259 girls (23.9%) students. Mean hemoglobin (P < 0.001), hematocrit (P < 0.001) and MCH (P < 0.01) were significantly different in men and women. No significant difference was observed in other hematological parameters among the two groups of students. This was a cross-sectional study conducted on 262 males and 259 females' students. The students were recruited from different Departments of Peshawar University through a convenience sampling procedure after taking informed consent. Students were interviewed and screened for the presence of anemia. Information was collected about socio-demographic background like age and sex on predesigned questionnaire. Blood specimens were collected in EDTA vacutainers and analyzed by using Hematolgy Analyser Huma Reader Plus. The data was analyzed by using computer software package SPSS version 10.0. To evaluate prevalence of anemia in male and female students of the university of Peshawar.